Microwave Technology, Its Use and Heating of Composite Aerated Concrete Blocks - Jiroušek, Zdeněk; Sobotka, Jindřich; Švecová, Táňa; Novotný, Miloslav (MDPI, 2023)
This paper aims to test the method of using microwave technology for drying aerated concrete masonry. Furthermore, the propagation of microwave technology through irradiated elements and the effectiveness of eliminating the moisture of the given blocks were examined. There are various discussions about the potential use of this technology in civil engineering. However, they are often based on inaccurate, superficial knowledge. The cause is usually based on a lack of access to accurate professional knowledge. Although the potential use of microwave technology (MWT) has been known for many decades, its use in civil engineering tends to be of marginal interest. The research and tests are mostly carried out by private facilities, which protect the obtained knowledge as their "know how". For this reason, VUT Brno teamed up with an implementation company and conducted several dozen experiments with repeated measurements of the effect of MWT on various building materials. Moreover, a number of different tests with drying of building materials, as well as the elimination of biotic pests in buildings have been carried out. However, the vast majority were experiments carried out in laboratory conditions, i.e., under precisely given boundary conditions, which were often very far from the conditions in real construction practice. Therefore, the goal of this experiment was to verify the use of microwave technology during the drying and heating of building materials. The experiments on the heating and drying of aerated concrete parts were divided into several phases, in which the dependence of the depth of heating on the time intervals of irradiation was verified. It was clearly concluded that the drying of this material by microwaves is very effective and efficient, particularly from time and financial viewpoints. Therefore, this technology can be successfully used in construction practice, which has started to be often used with reconstructions.

This paper aims to test the method of using microwave technology for drying aerated concrete masonry. Furthermore, the propagation of microwave technology through irradiated elements and the effectiveness of eliminating the moisture of the given blocks were examined. There are various discussions about the potential use of this technology in civil engineering. However, they are often based on inaccurate, superficial knowledge. The cause is usually based on a lack of access to accurate professional knowledge. Although the potential use of microwave technology (MWT) has been known for many decades, its use in civil engineering tends to be of marginal interest. The research and tests are mostly carried out by private facilities, which protect the obtained knowledge as their "know how". For this reason, VUT Brno teamed up with an implementation company and conducted several dozen experiments with repeated measurements of the effect of MWT on various building materials. Moreover, a number of different tests with drying of building materials, as well as the elimination of biotic pests in buildings have been carried out. However, the vast majority were experiments carried out in laboratory conditions, i.e., under precisely given boundary conditions, which were often very far from the conditions in real construction practice. Therefore, the goal of this experiment was to verify the use of microwave technology during the drying and heating of building materials. The experiments on the heating and drying of aerated concrete parts were divided into several phases, in which the dependence of the depth of heating on the time intervals of irradiation was verified. It was clearly concluded that the drying of this material by microwaves is very effective and efficient, particularly from time and financial viewpoints. Therefore, this technology can be successfully used in construction practice, which has started to be often used with reconstructions.
Microwave Technology, Its Use and Heating of Composite Aerated Concrete Blocks
Keywords: biotic pests; building materials; drying time; electromagnetic radiation; heating cooling; high frequency; irradiation; microwave technology; wall; biotic pests; building materials; drying time; electromagnetic radiation; heating cooling; high frequency; irradiation; microwave technology; wall